2013
DOI: 10.3109/14767058.2013.858689
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prenatal and postnatal treatments of spina bifida in Poland – a non-randomized, single-center study

Abstract: Prenatal MMC closure significantly lowers further adverse evolution of the II CM. Further studies are needed, especially on preventive measures for preterm labor and iatrogenic preterm prelabor rupture of membranes (iPPRM) in the postoperative course of IUMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 23 publications
7
78
1
1
Order By: Relevance
“…The patients reported on by Graf et al [26], Pedreira et al [27], Degenhardt et al [28], Verbeek et al [29], and Belfort et al [24] underwent fetoscopic repair of MMC. The patients reported on by Danzer et al [30], Friszer et al [31], Moldenhauer et al [32], Zamłyński et al [33], Bennett et al [34], and Hisaba et al [35] underwent open fetal repair of MMC. For each of the 11 studies, the data The patients reported on by Degenhart et al [28] overlap with those reported on by Kohl [12] in 2014, and the patients reported on by Verbeek et al [29] overlap with those reported on by Kohl et al [11] in 2010.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The patients reported on by Graf et al [26], Pedreira et al [27], Degenhardt et al [28], Verbeek et al [29], and Belfort et al [24] underwent fetoscopic repair of MMC. The patients reported on by Danzer et al [30], Friszer et al [31], Moldenhauer et al [32], Zamłyński et al [33], Bennett et al [34], and Hisaba et al [35] underwent open fetal repair of MMC. For each of the 11 studies, the data The patients reported on by Degenhart et al [28] overlap with those reported on by Kohl [12] in 2014, and the patients reported on by Verbeek et al [29] overlap with those reported on by Kohl et al [11] in 2010.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Incomplete outcome data were reported by Moldenhauer et al [32] and Zamłyński et al [33]. Of the 101 patients who were taken to the operating room for open fetal repair of MMC in the study by Moldenhauer et al [32], 2 patients were excluded from analysis of the outcomes as these 2 pregnancies were still ongoing.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the next report, concerning 31 IUMR cases, control fetal MRI revealed that 13 out of 19 fetuses demonstrated HH reduction and no progression was noticed in 6 cases [26]. In our non-randomized study, we compared a group of 46 fetuses treated in utero to 47 patients with MMC postnatal closure [28]. In this observation up to 53 months of life, decreased VPS implantation rate the first group (27.8% vs. 80%; CI 0.35, 0.16-0.75; p < 0.008), lower HH (11% vs. 70%; CI 0.16, 0.04-0.06, p < 0.01), and better motor function were noticed in the first group.…”
Section: Fmmc Repair -Polish Clinical Experiencementioning
confidence: 99%